PENGARUH TINGKATAN PRODUK TERHADAP LOYALITAS PELANGGAN: THE EFFECT OF PRODUCT LEVEL ON CUSTOMER LOYALTY - Muhammad Sutio (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The purpose study is to reveal the affect of core benefit, basic product, expected product, augmented product and potential product on the costumer loyalty both simultaneusly and partially. Study is belong to quantitative research where data collection used survey method and questionnaires is the instrument for data gathering. Samples consist of 100 unit. Analysis tool uses multiple regression analysis. The results showed that 1) core benefit, basic product, expected product, augmented product and potential product simultaneously affect costomer loyalty. Furthermore, partially those variables have significant affect too. Keywords: Core benefit, basic product, expected product, augmented product and potential product and costumer loyalty